Karakterisasi Bakteri Asam Laktat Proteolitik pada Bekasam - Wikandari, Prima Retno; Suparmo, Suparmo; Marsono, Yustinus; Rahayu, Endang Sutriswati (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Riau, 2012)
Bekasam is a traditional fermented fish from Indonesia. It is made from fish in which the gills and gut had been discarded, washed, and mixed with salt, after two days, it was covered with rice and salt, and then fermented for 5-7 days at room temperature. Bekasam is perceived to have antihypertensive activity, which is though to be the activity of bioactive peptides, the product of protein degradation during the bekasam fermentation. The research was aim to isolate the indigenous lactic acid bacteria that produce strong proteolytic capabilities. The lactic acid bacteria were collected from 3 kinds of bekasam (tilapia, milkfish, and tuna bekasam). Isolation of the lactic acid bacteria was done on agar medium containing MRS + CaCO3, and the screening of the proteolytic bacteria was done by growing the isolated culture on skim agar. The colonies that produce clear zone were identified as proteolytic lactic acid bacteria. Some of 180 isolated strains of acid producing bacteria that produce clear zone on MRS agar were found 150 strains of lactic acid bacteria, and 84 strains showed their proteolytic activity. The later were identified morphologically and biochemical as Lactobacillus, Pediococcus and Leuconostoc genera. Selection was further conducted based on the height of the proteolytic and homofermentative fermentation activities. Upon species identification using API CH 50 kit, the selected strains belong to species of Lactobacillus plantarum, Lactobacillus pentosus, and Pediococcus pentosaseus.